2018
DOI: 10.1186/s12929-018-0421-9
|View full text |Cite
|
Sign up to set email alerts
|

MEKK1, JNK, and SMAD3 mediate CXCL12-stimulated connective tissue growth factor expression in human lung fibroblasts

Abstract: BackgroundIn idiopathic pulmonary fibrosis, the interaction of CXCL12 and CXC receptor 4 (CXCR4) plays a critical role in lung fibrosis. Connective tissue growth factor (CTGF) overexpression underlies the development of pulmonary fibrosis. Our previous report showed that the Rac1-dependent extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), and activator protein (AP)-1 pathways are involved in CXCL12-generated CTGF expression in human lung fibroblasts (WI-38). In present study, we addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…However, with a chronic persistent inflammatory stimulus such as cigarette smoking, it could promote proliferation of structural cells such as fibroblasts and their production of pro-inflammatory cytokines such as IL-8, vascular endothelial growth factor (VEGF), and transforming growth factor alpha (TGF-α) with augmented expression in chronic inflammatory conditions such as rheumatoid arthritis [50]. Mitogen-activated protein kinase 5 (MAP3K5) is a member of MAP kinase family that activates c-Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinases to an array of stresses such as oxidative stress, endoplasmic reticulum stress and calcium influx [51][52][53]. It has been implicated in the pathogenesis of chronic inflammatory conditions such as rheumatoid arthritis, cardiopulmonary diseases and diabetes [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…However, with a chronic persistent inflammatory stimulus such as cigarette smoking, it could promote proliferation of structural cells such as fibroblasts and their production of pro-inflammatory cytokines such as IL-8, vascular endothelial growth factor (VEGF), and transforming growth factor alpha (TGF-α) with augmented expression in chronic inflammatory conditions such as rheumatoid arthritis [50]. Mitogen-activated protein kinase 5 (MAP3K5) is a member of MAP kinase family that activates c-Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinases to an array of stresses such as oxidative stress, endoplasmic reticulum stress and calcium influx [51][52][53]. It has been implicated in the pathogenesis of chronic inflammatory conditions such as rheumatoid arthritis, cardiopulmonary diseases and diabetes [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CXCL12/CXCR4 activation through multiple downstream pathways leads to increased cell proliferation and migration, such as NF-κB [31] and PI3K/Akt [32] pathway activation. CXCL12/CXCR4 can act on MAPK pathway through G protein and then act on its downstream ERK1/2 and FAK to cause cell chemotaxis and inflammatory cytokine accumulation [3336].…”
Section: Discussionmentioning
confidence: 99%
“… 21 24 Signaling via the CXCL12/CXCR4 axis also resulted in the activation of Smad3 via MAPK. 42 The results presented here revealed that ALK5 may be among the downstream targets of CXCR4 and may be capable of CXCR4 transactivating ALK5. However, whether the activation of Smad3 in the non-canonical pathway depends on MAPK also remains unclear; further experiments will be needed in order to clarify this point.…”
Section: Discussionmentioning
confidence: 53%